Pengaruh Penambahan Tepung Jahe (Zingiber officinale) terhadap pH dan Warna Telur Ayam Asin - Pundiswara, Dimas Adhie; Sumarmono, Juni; Sentosa, Singgih Sugeng (ANGON: Journal of Animal Science and Technology, 2021)
Background. The study entitled "The effect of adding ginger flour (zingiber officinale) to the pH and color of chicken eggs. Materials and methods. The research was conducted on April 12 – April 30, 2021, at the Laboratory of Animal Products Technology, Faculty of Animal Husbandry, Jenderal Sudirman University, Purwokerto. The study was conducted using a completely randomized design method with 4 treatments and 5 replications. The influential variables were continued by further testing of orthogonal polynomials. The treatments tested were the addition of ginger flour, namely, P1: 0% ginger flour, P2: 10% ginger flour, P3: 20% ginger flour, P4: 30% ginger flour. Egg color was measured using a colorimeter, egg pH using a pH meter, and data analysis using analysis of variance. Results. The results showed that the average pH of egg whites (albumen) ranged from 6.92 to 7.33, the average pH of egg yolks ranged from 5.98 to 6.17, while the average egg white color was 55.93 – 66.71, and the average egg yolk ranged from 21.89 to 27.82. The results showed that the addition of ginger flour did not affect the pH of the egg yolk and the pH of the egg white. Conclusion. The addition of ginger flour in the manufacture of salted chicken eggs resulted in the same albumen color, while the addition of 20% ginger flour for the yolk caused the egg yolk color to become redder.